2020
DOI: 10.3389/fmed.2020.00047
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Understanding the Effects of Erythropoietin on Renal Fibrosis

Abstract: Renal fibrosis is the common manifestation of the pathogenesis of end-stage renal disease that results from different types of renal insult, and is a hallmark of chronic kidney disease (CKD). The main pathologic characteristics of renal fibrosis are renal interstitial fibroblast hyperplasia and the aberrant and excessive deposition of extracellular matrix, pathologies that lead to the destruction of normal renal tubules and interstitial structures. However, the biological significance of fibrosis during the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Effective prevention and treatment of RF are of great significance for delaying the progression of kidney disease and reducing the occurrence of uremia. However, currently, there is no effective treatment for preventing and reversing RF [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effective prevention and treatment of RF are of great significance for delaying the progression of kidney disease and reducing the occurrence of uremia. However, currently, there is no effective treatment for preventing and reversing RF [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was reported that the activation of the Pi3K/AKT pathway slows down tubular healing and increases renal fibrosis in IR injury-induced acute kidney injury. On the contrary, the treatment with EPO in the same model is associated with the prevention of programmed cellular death 51 . Our outcomes adhere to the aforementioned data in which the TAA-enhanced renal injury was associated with the activation of JAK2/PI3K/STAT5, another indirect pathway of STAT5 activation.…”
Section: Discussionmentioning
confidence: 96%
“…34 Furthermore, it has been reported that EPO-H enhances the revival in acute kidney injury (AKI), and it improves proteinuria and blood biomarkers of kidney injury in CKD patients. 35 ESAs have essential protective effects on the kidneys and improve the prognosis in CKD patients. 36 These effects of ESAs were not supported by a study that reported EPO-receptor (EPO-R) protein was almost undetectable in renal cells, and there was no evidence of EPO-R expression and function in the studied group.…”
Section: Treatment ( Fig 1 )mentioning
confidence: 99%